The impact of tumor characteristics on cardiovascular disease death in breast cancer patients with CT or RT: a population-based study - Chi, Kaiyi; Luo, Zehao; Zhao, Hongjun; Li, Yemin; Liang, Yinglan; Xiao, Zhaoling; He, Yiru; Zhang, Hanbin; Ma, Zaiying; Zeng, Liangjia; Zhou, Ruoyun; Feng, Manting; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Previous studies focused on the impact of cardiovascular diseases (CVD) risk factors in breast cancer patients with chemotherapy (CT) or radiotherapy (RT). This study aimed to identify the impact of tumor characteristics on CVD death in these patients. Methods Data of female breast cancer patients with CT or RT between 2004 and 2016 were included. The risk factors of CVD death were identified using Cox regression analyses. A nomogram was constructed to evaluate the predicted value of tumor characteristics, and then validated by the concordance indexes (C-index) and calibration curves. Result A total of 28,539 patients were included with an average follow-up of 6.1 years. Tumor size > 45 mm (adjusted HR = 1.431, 95% CI = 1.116–1.836, P = 0.005), regional (adjusted HR = 1.278, 95% CI = 1.048–1.560, P = 0.015) and distant stage (adjusted HR = 2.240, 95% CI = 1.444–3.474, P < 0.001) were risk factors of CVD death for breast cancer patients with CT or RT. The prediction nomogram of tumor characteristics (tumor size and stage) on CVD survival was established. The C-index of internal and external validation were 0.780 (95% Cl = 0.751–0.809), and 0.809 (95% Cl = 0.768–0.850), respectively. The calibration curves showed consistency between the actual observation and nomogram. The risk stratification was also significant distinction (P < 0.05). Conclusion Tumor size and stage were related to the risk of CVD death for breast cancer patients with CT or RT. The management of CVD death risk in breast cancer patients with CT or RT should focus not only on CVD risk factors but also on tumor size and stage.